An Analysis of Taboo Language in Hip Hop Song Lyrics - Maisura, Vivi; Moetia, Meristika (English Language Teaching Methodology, 2025)
This study discusses the use of taboo language in hip-hop lyrics, focusing on its various types. The study aims to identify the types of taboo words, including cursing, profanity, obscenity, blasphemy, vulgar language, sexual harassment, name calling and insults in Cardi B songs lyrics. Data were collected through a text analysis of three songs by Cardi B, as well as a literature review on the linguistic and social functions of vulgar and taboo language. A thematic analysis was conducted to identify patterns in the use of taboo language within the context of hip-hop music. The results show that six out (cursing, profanity, obscenity, sexual harassment, vulgar language, name-calling and insults) of seven types of taboo language (cursing, profanity, obscenity, blasphemy, sexual harassment, vulgar language, name-calling and insults)  appear in Cardi B's lyrics, with two types appearing most frequently (cursing and profanity).